Penggunaan Metode System Usability Scale Untuk Mengukur Aspek Usability Pada Media Pembelajaran Daring di Universitas XYZ - Dorie P. Kesuma (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
This study aims to evaluate online learning media at XYZ University on the usability aspect using the System Usability Scale (SUS) method with 10 questions to measure the quality of the usability aspect of the LMS service. A total of 50 respondents from among students were involved in this study. The test results show the System Usability Scale (SUS) assessment is at an average score of 69.9. From these results, XYZ University's online learning media service received grade C, the percentile rating was in the range of 52%, included in the OK category for its nature aspect (Adjective), and included in the marginal category for its acceptance rate (Acceptable) and for its NPS value, classified as passive. This results place XYZ University's online learning media as a service that acceptable by it’s student. However, improvements are still needed to increase student satisfaction as service users, which can impact improving student learning outcomes.